1988
DOI: 10.1098/rspb.1988.0017
|View full text |Cite
|
Sign up to set email alerts
|

Pre-imaginal biasing of caste in a primitively eusocial insect

Abstract: Primitively eusocial insects often lack morphological caste differentiation, leading to considerable flexibility in the social and reproductive roles that the adult insects may adopt. Although this flexibility and its consequences for social organization have received much attention there has been relatively little effort to detect any pre-imaginal effects leading to a bias in the potential caste of eclosing females. Experiments reported here show that only about 50 % of eclosing females of the tropical social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…For example, in aculeate Hymenoptera the size of pollen balls constructed by the mother or the amount of food fed directly to the larvae determines o¡spring size and sometimes caste (e.g. Plowright & Jay 1968;Packer & Knerer 1985;Gadagkar et al 1988Gadagkar et al , 1990Frank & Crespi 1989; O'Donnell 1998; see also Field & Foster 1999). Moreover, among species of halictine bees, there is a close positive association between the extent to which subordinate workers are smaller than their mother, worker subfertility and female bias of the ¢rst brood (indicative of less dispersal by ¢rst-brood females or less queen supersedure) (Ordway 1965;Plateaux-Quenu 1967;Breed 1975Breed , 1976.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in aculeate Hymenoptera the size of pollen balls constructed by the mother or the amount of food fed directly to the larvae determines o¡spring size and sometimes caste (e.g. Plowright & Jay 1968;Packer & Knerer 1985;Gadagkar et al 1988Gadagkar et al , 1990Frank & Crespi 1989; O'Donnell 1998; see also Field & Foster 1999). Moreover, among species of halictine bees, there is a close positive association between the extent to which subordinate workers are smaller than their mother, worker subfertility and female bias of the ¢rst brood (indicative of less dispersal by ¢rst-brood females or less queen supersedure) (Ordway 1965;Plateaux-Quenu 1967;Breed 1975Breed , 1976.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work has demonstrated that Sitters and Fighters have significantly better-developed ovaries compared to the Foragers and that there are no significant body size differences between the behavioral groups (Chandrashekara and Gadagkar,199la). Nor is body size a good predictor of the ability of isolated laboratory females to develop their ovaries and lay eggs (Gadagkar et al, 1988). …”
Section: Behavioral Differentiation and Queen Successionmentioning
confidence: 99%
“…We suspect that it is a combination of physiological and ecological factors. We have evidence that female wasps in R. marginata have extremely variable reproductive potential [14] and at least half of them fail to build nests and lay eggs in spite of having all the resources to do so [15]. However, we do not fully understand the mechanism by which such variation in reproductive potential is produced.…”
Section: Ecological/physiological Predisposition (B B)mentioning
confidence: 96%
“…However, we do not fully understand the mechanism by which such variation in reproductive potential is produced. Among the ideas proposed, parental manipulation is a likely candidate [15][16][17][18]. We have evidence that the significantly lower productivity of forced single foundresses may also arise owing to their inability to forage and feed a large quantity of brood and yet survive as well as voluntary single foundresses.…”
Section: Ecological/physiological Predisposition (B B)mentioning
confidence: 99%